1977
DOI: 10.1139/v77-435
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses in the group of Nuphar alkaloids. III. Total synthesis of (±)-nupharamine and (±)-3-epinupharamine

Abstract: The alkaloids (±)-nupharamine and (±)-3-epinupharamine were synthesized using 3-acetylfuran as the starting material. The conditions for stereoselective reduction of pyridine derivatives are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Since the length of the carbon chain in 3 is fixed ( x + y = 8), the availability of both converging alkenes, the piperidine 5 and the alkenoic acid 6 , must be considered. After searching the literature, we found that methods for preparing 2-substituted alkenyl piperidines are rarer for molecules in which the terminal olefin is more distant from the piperidine unit. In addition, commercial supplies of 8-nonenoic acid/alcohol and 7-octenoic acid/alcohol are very limited. In contrast, the key components of 4a and 4b are more easily obtained: the 2-allylpiperidine 5 has been reported by several groups, and its counterpart alkene is derived from 9-decenoic acid ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the length of the carbon chain in 3 is fixed ( x + y = 8), the availability of both converging alkenes, the piperidine 5 and the alkenoic acid 6 , must be considered. After searching the literature, we found that methods for preparing 2-substituted alkenyl piperidines are rarer for molecules in which the terminal olefin is more distant from the piperidine unit. In addition, commercial supplies of 8-nonenoic acid/alcohol and 7-octenoic acid/alcohol are very limited. In contrast, the key components of 4a and 4b are more easily obtained: the 2-allylpiperidine 5 has been reported by several groups, and its counterpart alkene is derived from 9-decenoic acid ( 6 ).…”
Section: Introductionmentioning
confidence: 99%